2015
DOI: 10.7314/apjcp.2015.16.8.3539
|View full text |Cite
|
Sign up to set email alerts
|

Parotid Gland Tumours in Turkish Population: Analysis of 165 Patients

Abstract: Background: Retrospective data on 165 patients who presented with a parotid mass and underwent surgery in our clinics during 2000-2009 were examined. The obtained data (demographic data, surgical procedures, histopathological diagnoses) were compared to similar studies to make contributions to the literature. Materials and Methods: Patients were classified according to their histopathological diagnosis. Surgical procedures and patient follow-up were clarified. The results are presented as means and standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Approximately 80% of parotid lesions are benign, and approximately 20% are malignant . The most common of the benign tumors include pleomorphic adenoma (59%) and Warthin tumor (22%) . Although pleomorphic adenoma affects predominantly females (60%), Warthin tumors are found more often in males than in females .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80% of parotid lesions are benign, and approximately 20% are malignant . The most common of the benign tumors include pleomorphic adenoma (59%) and Warthin tumor (22%) . Although pleomorphic adenoma affects predominantly females (60%), Warthin tumors are found more often in males than in females .…”
mentioning
confidence: 99%
“…3,4 The most common of the benign tumors include pleomorphic adenoma (59%) and Warthin tumor (22%). 5 Although pleomorphic adenoma affects predominantly females (60%), Warthin tumors are found more often in males than in females. 4 The most common malignant tumors of the parotid glands are mucoepidermoid carcinoma and adenoid cystic carcinoma.…”
mentioning
confidence: 99%
“…In the treatment of parotid cancers, all studies confirm the improvement in prognosis when surgery and radiotherapy are combined, rather than surgery alone or radiotherapy alone [16].…”
Section: Discussionmentioning
confidence: 84%
“…Swelling of the parotid region was the most frequent reason for consultation in all patients (100%) in our series, associated in rare cases with peripheral facial paralysis in 3 patients (9.67%). Several series have also shown that swelling of the parotid region was the main symptom [16] [17] [18]. Clinical examination pro-vides evidence of benignity (firm, mobile, painless) or malignancy (fixed, painful, adenopathies) [19].…”
Section: Discussionmentioning
confidence: 99%